Multiscale simulation approach to investigate the binder distribution in catalyst layers of high-temperature polymer electrolyte membrane fuel cells - Kwon, Sung Hyun; Lee, So Young; Kim, Hyoung Juhn; Yim, Sung-Dae; Sohn, Young-Jun; Lee, Seung Geol (Nature Publishing Group, 2022)
A multiscale approach involving both density functional theory (DFT) and molecular dynamics (MD) simulations was used to deduce an appropriate binder for Pt/C in the catalyst layers of high-temperature polymer electrolyte membrane fuel cells. The DFT calculations showed that the sulfonic acid (SO3-) group has higher adsorption energy than the other functional groups of the binders, as indicated by its normalized adsorption area on Pt (similar to 0.1078 eV/angstrom(2)) and carbon (similar to 0.0608 eV/angstrom(2)) surfaces. Consequently, MD simulations were performed with Nafion binders as well as polytetrafluoroethylene (PTFE) binders at binder contents ranging from 14.2 to 25.0 wt% on a Pt/C model with H3PO4 at room temperature (298.15 K) and operating temperature (433.15 K). The pair correlation function analysis showed that the intensity of phosphorus atoms in phosphoric acid around Pt (rho pgpt-p(r)) increased with increasing temperature because of the greater mobility and miscibility of H3PO4 at 433.15 K than at 298.15 K. The coordination numbers (CNs) of Pt-P(H3PO4) gradually decreased with increasing ratio of the Nafion binders until the Nafion binder ratio reached 50%, indicating that the adsorption of H3PO4 onto the Pt surface decreased because of the high adsorption energy of SO3- groups with Pt. However, the CNs of Pt-P(H3PO4) gradually increased when the Nafion binder ratio was greater than 50% because excess Nafion binder agglomerated with itself via its SO3- groups. Surface coverage analysis showed that the carbon surface coverage by H3PO4 decreased as the overall binder content was increased to 20.0 wt% at both 298.15 and 433.15 K. The Pt surface coverage by H3PO4 at 433.15 K reached its lowest value when the PTFE and Nafion binders were present in equal ratios and at an overall binder content of 25.0 wt%. At the Pt (lower part) surface covered by H3PO4 at 433.15 K, an overall binder content of at least 20.0 wt% and equal proportions of PTFE and Nafion binder are needed to minimize H3PO4 contact with the Pt.